FI-STAR Online Personalised Cardiac Rehabilitation Solution - Busnatu, Stefan Sebastian; Sinescu, Crina Julieta (International Journal of Online and Biomedical Engineering (iJOE), 2015)
Background:Advanced disease prevention solutions using telemedicine are vital for the future in order to decrease the burden produced by the cardio-vascular diseases. This solutions need to ensure more accessibility, high performance and good data privacy.Material and Method:Study groups consist of 48 acute myocardial infarction patients: 24 home monitored using telemedicine and 24 control group performing unmonitored rehabilitation. The process will have two phases: the inpatient period will be common (5-7 days) and the outpatient period (7 weeks). The monitored group will receive a set of Bluetooth capable monitoring devices at discharge, a blood pressure device, a cardio watch, a pulsoxymeter, an ECG chest strap and a Smartphone with the application installed. The application that will be built from scratch will contain the nutritional, medical and physical activity plan and also has monitoring and treatment adjustment functions by the medical personnel Results: Before hospital discharge and at the end of the program all patients will perform an ECG treadmill test, which summed with other medical investigations, will quantify the cardiac fitness level and their improvement. Also using a MAST personalized model there will be assessed a set of performance indicators.Conclusions: The Online Cardiac rehabilitation solution will be a light and secure software, built using Specific Enablers, technology created as generic enablers in the FI-WARE project. This is hoped to offer more patient independence, improve their cardiac fitness and quality of life and reduces the high cost that cardiovascular disease brings to the medical system.